Economical, political, and social issues in water resources - Bozorg-Haddad, Omid, 1974- (Elsevier, 2021)
Economical, Political, and Social Issues in Water Resources provides a fully comprehensive and interdisciplinary overview of all three factors in their relation to water resources. Economic issues consist of Water accounting, Water economy, Water pricing, Water market, Water bank and bourse. Political issues consist of Water power and hydrogemistry, Water diplomacy and hydropolitics, Water rights and water laws, Water governance and policy, Shared water resources management, Water management systems, and social issues consist of Water and culture, civilization and history, Water quality, hygiene, and health, Water and society. This book familiarizes researchers with all aspects of the field, which can lead to optimized and multidimensional water resources management. Some of abovementioned issues are new, so the other aim of this book is to identify them in order to researchers can easily find them and use them in their studies. Includes diverse case studies from around the world Presents contributions from global and diverse contributors with interdisciplinary backgrounds, including water engineers, scientists, planners the economic, political and social issues surrounding water Contains in-depth definitions and concepts of each topic.